KAIN TENUN BADUY SEBAGAI POTENSI INDIKASI GEOGRAFIS DI KABUPATEN LEBAK PROVINSI BANTEN: Baduy Woven Fabric as a Potential Geograpihical Indication in Lebak Regency, Banten Province - Irfana, Ardhana Berlin; Desmayanti, Rakhmita (AMICUS CURIAE, 2025)
Baduy Woven Fabric as one of the potential geographical indications in Lebak Regency, Banten Province has advantages and historical value that is closely related to the culture of the Baduy tribe. The Baduy people consider woven cloth to be an important part of their life. Every detail of cloth making is full of meaning because it has a philosophical basis. This research aims to to find out whether it is appropriate for Baduy Woven Cloth to be registered as a Geographical Indication Intellectual Property and receive legal protection from the Government. The research uses normative legal research methods, with secondary data supported by primary data. Based on the results of the research, it i known that based on Article 1 paragraph 6 of the Goverment Regulation Number 56 of 2022 concerning Communal Intellectual Property, the Baduy Weaving Cloth qualifies as a potential geographical indication and worthy of legal protection to ensure necessary security for the community to enjoy their legal rights, uphold human rights, and prevent threats against these rights.